PENGARUH NET PROFIT MARGIN, PERTUMBUHAN PERUSAHAAN, DAN DEBT TO ASSET RATIO TERHADAP HARGA SAHAM DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN PERTAMBANGAN BATU BARA YANG TEDAFTAR DI BEI TAHUN 2022-2024 - Eliza Khairotun Nisak; Ika Wahyuni; Febri Ariyantiningsih (Jurnal Mahasiswa Entrepreneurship (JME), 2026)
The purpose of this study is to analyze and test the effect of Net Profit Margin, Company Growth, and Debt to Asset Ratio on Stock Price with Dividend Policy as an intervening variable. The object of this study is a coal mining company listed on the Indonesia Stock Exchange in 2022-2024. The analytical method used is Partial Least Squares (PLS) using the Smart PLS 3.0 application, which includes classical assumption tests, including multicollinearity and normality tests, coefficient of determination tests, structural equation analysis (Inner Model), and research hypothesis testing. The results of the study indicate that Net Profit Margin has a positive but insignificant effect on Dividend Policy and Stock Price. Company Growth has a significant negative effect on Dividend Policy, while Debt to Asset Ratio has a negative but insignificant effect on Dividend Policy. Furthermore, Company Growth has a negative but insignificant effect on Stock Price, but Debt to Asset Ratio has a positive but insignificant effect on Stock Price. Then, Dividend Policy is also proven to have a negative but insignificant effect on Stock Price. The results of the indirect effect hypothesis test indicate that Net Profit Margin has a negative but insignificant effect on Stock Price through Dividend Policy. Meanwhile, company growth and Debt to Asset Ratio have a positive but insignificant influence on stock prices through dividend policy.